Die Majorität der an sJIA erkrankten Kinder ist wohlauf (Aktuelle Rheumatologie, 2017)
Janov G et al. The Systemic Juvenile Idiopathic Arthritis Cohort of the Childhood Arthritis and Rheumatology Research Alliance Registry: 2010–2013.